New trade union activism. Class consciousness or social identity? - Moore, Sian (Basingstoke, 2011)
"New trade union roles and contexts have encouraged the emergence of new representatives and provided the basis for a more diverse activism. This book asks whether trade union activity and ideologies allow for the expression and mobilisation of different social identities and whether, in a changed and changing economic and political context, these eclipse class. Based upon the voices of the activists themselves, this book restores the subject to the landscape of industrial relations. It reasserts the centrality of work and the workplace to social identity, but emphasizes the importance of gender, race and ethnicity to changing work relations and consequently to the production of collective identity and consciousness. Yet new activism may be articulated in rather abstract concepts of equality and fairness, distinct from earlier more assertive and politically focused collective mobilization of politically conscious identities which characterized the self-organisation of social movements, but also from the language and vocabulary of class consciousness – reflecting legacies of political defeat.